Effects of mecamylamine on nicotine-induced conditioned hyperactivity and sensitization in differentially reared rats - Ha, Rosemary (Kansas State University, 2008)
Rats reared in an enriched condition (EC) with novel stimuli and social contact with cohorts display less sensitization to nicotine than rats reared under impoverished conditions (IC). However, it is currently unknown what effect differential rearing has on nicotine-induced conditioned hyperactivity. The present study determined whether differential rearing affects conditioning to a nicotine-associated context. In addition, this study also examined the effects of mecamylamine, an antagonist to nicotinic acetylcholine receptors, on conditioned hyperactivity and sensitization. This antagonistic drug has been shown to attenuate the locomotor effects of nicotine. In the current study, EC, IC, and social condition (SC) rats were reared from 21 to 51 days of age before training for the acquisition of conditioned hyperactivity and sensitization. Nicotine (0.4 mg/kg) was administered prior to 1-h locomotor sessions. Conditioned hyperactivity testing followed. Rats then received 5 sessions of sensitization training followed by a 16-day drug-free rest period before being tested for sensitization. Mecamylamine (1.0 mg/kg) was administered to rats prior to the conditioned hyperactivity test and sensitization test. Nicotine treatment resulted in sensitization and conditioned hyperactivity in all differential rearing groups. EC rats displayed less locomotor activity in response to nicotine than both IC and SC rats. Pretreatment with mecamylamine blocked the expression of conditioned hyperactivity in EC and SC rats and attenuated sensitization in all three rearing groups. These findings suggest that environmental enrichment may alter nAChR binding during development and may be a protective factor in the initiation and relapse of smoking behavior.
Keywords: Nicotine; Environmental Enrichment; Conditioned Hyperactivity; Sensitization; Mecamylamine; Psychology, Psychobiology (0349)